A multi-directional analysis of the centre of resistance using finite element model of the human mandibular canine - Elaheh Kamali; Amirreza Geramy; Allahyar Geramy (Clinical and Investigative Orthodontics, 2025)
Purpose The most important factor determining the quality of orthodontic tooth movement is the relationship between the force and the tooth centre of resistance (CRes). Tooth-supporting structure affect the centre of resistance location and their features vary in different areas around the specific tooth. So the aim of this study is the multi-planar analysis of the CRes using finite element models of the human mandibular canine to find the exact location of the CRes when viewed from different aspects.Methods The left mandibular canine, periodontal ligament, cortical bone, and spongy bone designed in Solidworks (version 2021) according to a contralateral canine with a complete eruption in a case with an impacted canine which has been ordered for CBCT. the tooth dimension was slightly modified according to the wheeler’s dental anatomy. The meshed model was created. A 1 N.mm couple was applied to the model and the CRes was evaluated from different 24 planes with 15 degrees intervals.Results The location of the human mandibular centre of resistance differs in a horizontal plane when evaluated in different directions. It is 46% to 86% of canine root length from the apex and has different occlusogingival locations in various planes up to 4.48 mm. The CRes location was more apical In the buccal or lingual directions than mesial or distal.Conclusion The location of the CRes changes when evaluated in different directions related to supporting tissue features. It can be concluded that canine requires a higher M/F for buccolingual translation than for mesiodistal translation